Diverse Properties of Carbon-Substituted Silicenes - Pham, Hai Duong; Lin, Shih-Yang; Gumbs, Godfrey; Khanh, Nguyen Duy; Lin, Ming-Fa (Frontiers in Physics, 2020)
The theoretical framework, which is built from the first-principles results, is successfully developed for investigating emergent two-dimensional (2D) materials, as it is clearly illustrated by carbon substitution in silicene. By the delicate VASP calculations and analyses, the multi-orbital hybridizations are thoroughly identified from the optimal honeycomb lattices, the atom-dominated energy spectra, and the spatial charge density distributions the atom & orbital-decomposed van Hove singularities, being very sensitive to the concentration and arrangements of guest atoms. All the binary 2D silicon-carbon compounds belong to the finite- or zero-gap semiconductors, corresponding to the thoroughly/strongly/slightly modified Dirac-cone structures near the Fermi level. Additionally, there are frequent π and σ band crossings, but less anti-crossing behaviors. Apparently, our results indicate the well-defined π and σ bondings.